Method for manufacturing thermal sprayed film-coated member and thermal sprayed film-coated member
By adjusting the spatial volume ratio of the surface of the ceramic sintered body substrate to the particle size ratio of the ceramic raw material powder, and using non-oxidized gas plasma spraying technology, the adhesion and strength of the thermal spray film on the surface of the ceramic substrate is solved, and a stable ceramic spray film formation is achieved.
Patent Information
- Application Number
- JP2020175381
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Priority Date
- 2019-11-01
- Filing Date
- 2020-10-19
- Publication Date
- 2025-02-07
- Estimated Expiration
- 2040-10-19
AI Technical Summary
In the prior art, when preparing a surface thermal spray film of ceramic substrate, there is a risk of decrease in substrate strength and damage. Especially when the surface roughening treatment is not performed, the adhesion between the ceramic substrate and the ceramic spray film is poor, making it difficult to effectively form chemical bonds.
By adjusting the spatial volume ratio of the surface of the ceramic sintered body substrate to the average particle size ratio of the ceramic raw material powder, plasma spraying is used to avoid surface roughening and form a ceramic spray film.
The adhesion strength between the ceramic spray film and the substrate is improved, the strength decrease and damage risk of the substrate is reduced, and the stable formation of the ceramic spray film is achieved.
Smart Images

Figure 0007627992000001 
Figure 0007627992000002 
Figure 0007627992000003
Abstract
Description
Technical Field
[0001] The present invention relates to a method for manufacturing a thermal spray film-coated member and a thermal spray film-coated member.
Background Art
[0002] For the purpose of protecting a base material and improving its functions, a thermal spray coating is formed on the surface of the base material. For example, in order to enhance the plasma resistance, wear resistance, heat insulation property, etc. of a ceramic base material formed of silicon carbide (SiC), aluminum oxide (Al2O3), aluminum nitride (AlN), etc., ceramics such as yttria (Y2O3), titania (TiO2), chromia (Cr2O3), etc. may be thermally sprayed.
[0003] Conventionally, in order to coat a ceramic thermal spray film on a base material, a process of roughening the surface of the base material to make the thermal spray film adhere before forming the thermal spray film has been essential. For example, it is possible to roughen the surface of the base material by blasting, but for non-metal base materials such as ceramic base materials, there is a risk of a decrease in the strength of the base material due to crack generation and breakage of the base material caused by cracks, so blasting may not be sufficient in some cases. Therefore, there has been a demand for a method of forming a ceramic film on a ceramic base material by thermal spraying without inducing cracks.
[0004] Patent Document 1 discloses a ceramic thermal spray coating member in which a SiC sintered body is roughened by blasting, then its surface is oxidized, and a Y2O3 thermal spray film is formed thereon, so that SiO2 and Y2O3 formed by oxidation form a complex oxide and are bonded at the atomic level to adhere closely. Patent Document 2 discloses a method for manufacturing a thermal spray coating member in which a thin oxide film SiO2 layer is formed on the surface of a SiC base material by irradiating it with a laser, filling microcracks, and obtaining chemical adhesion between the oxide film and an Al2O3 thermal spray film. Patent Document 3 discloses a slurry and a thermal spraying method in which Al is used for the base material and 0.4 < D10 / Ra ≦ 0.9 in the relationship between the particle size D10 of the slurry raw material and the base material.
Prior Art Documents
[0005] [Patent Document 1] JP 2014-162934 A [Patent Document 2] WO2016 / 170895 [Patent Document 3] JP 2018-154895 A Summary of the Invention [Problem to be solved by the invention]
[0006] However, Patent Document 1 limits the materials that can be used as the substrate and the thermal spray coating to materials that contain silicon and have a higher melting point than the siliceous layer, respectively, making it difficult to apply to general ceramic substrates and ceramic spray materials. Also, Patent Document 2 uses a material that is prone to forming an oxide film by laser irradiation as the substrate, making it difficult to apply to general ceramic substrates.
[0007] Furthermore, although Patent Document 3 describes that ceramics can be used for the substrate, the experiments were actually conducted on an aluminum substrate, and it is unclear whether similar results can be obtained with the combination of a ceramic substrate and a ceramic sprayed coating, which tends to have weak adhesion.
[0008] The present invention has been made in consideration of the above circumstances, and has an object to provide a method for manufacturing a sprayed film-coated member that can improve the adhesion strength of a ceramic sprayed film and reduce the risk of a decrease in the substrate material strength of the ceramic sintered body substrate and damage to the substrate, even when blasting is not performed on a substrate made of a ceramic sintered body. [Means for solving the problem]
[0009] (1) In order to achieve the above object, the method for producing a thermal sprayed film-coated member of the present invention comprises the steps of:SiC, AlN, or Al 2 O 3 A sintered body comprising The spatial volume Vvv (μm 3 / μm 2 ) to a predetermined range, and a coating process for coating the surface to be sprayed of the substrate by plasma spraying with a slurry made of water and a ceramic raw material powder having an average particle diameter D50 in the range of 0.5 μm to 6 μm, wherein the adjusting process is performed to adjust the spatial volume Vvv and the average particle diameter D50 to a value within a range of 0.001≦(Vvv / (D50) 3 )≦0.40.
[0010] This allows the sprayed film to adhere to the substrate without the need for a process of roughening the substrate surface by blasting, thereby reducing the risk of a decrease in substrate material strength or damage to the substrate caused by blasting a ceramic substrate.
[0011] (2) In the method for producing a thermal sprayed film-coated member of the present invention, the ceramic sintered body is a SiC sintered body, which is a brittle material that does not adhere well to other ceramic materials, and thus a ceramic sprayed film can be formed on the SiC sintered body while reducing the risk of a decrease in the strength of the substrate material or damage to the substrate.
[0012] (3) In the method for producing a thermal sprayed film-coated member of the present invention, the ceramic sintered body is an Al2O3 sintered body, which is a brittle material that does not adhere well to other ceramic materials. This makes it possible to form a ceramic thermal sprayed film on the Al2O3 sintered body while reducing the risk of a decrease in the strength of the substrate material or damage to the substrate.
[0013] (4) In the method for producing a thermal sprayed film-coated member of the present invention, the ceramic sintered body is an AlN sintered body, which is a brittle material that does not adhere well to other ceramic materials. This makes it possible to form a ceramic thermal sprayed film on the AlN sintered body while reducing the risk of a decrease in the strength of the substrate material or damage to the substrate.
[0014] (5) In the method for producing a thermal sprayed film-coated member of the present invention, the plasma spraying is characterized by using a non-oxidizing gas, which prevents unnecessary oxidation of the substrate surface and prevents oxidation deterioration of the thermal spray gun parts, thereby enabling stable thermal spraying with secured adhesion.
[0015] (6) In the method for producing a thermal spray coated member of the present invention, the ceramic raw material powder is a powder of alumina, yttria, zirconia, titania, chromia, and yttrium-alumina-garnet, or a mixture of any of these powders. These materials may not adhere well to substrates made of other ceramic materials, but the production method of the present invention allows them to adhere firmly to the ceramic substrate.
[0016] (7) In the method for producing a thermal sprayed film-coated member of the present invention, the spatial volume Vvv is 0.01 or more and 0.30 or less. This makes it possible to adjust the spatial volume Vvv of the thermal sprayed surface of the ceramic sintered body substrate to a predetermined range by polishing or grinding.
[0017] (8) The present invention also provides a thermal sprayed film-coated member comprising a ceramic sintered body substrate and a thermal sprayed film provided on a surface to be thermal sprayed of the ceramic sintered body substrate, the spatial volume Vvv (μm 3 / μm 2 ), and the ceramics forming the thermal sprayed film. of For average particle diameter D50 (μm), 0.001≦(Vvv / (D50) 3 )≦0.40, The ceramic sintered body substrate is made of SiC, AlN, or Al.2 O 3 A sintered body comprising: The thermal spray coating is characterized in that there is no chemical bond between the elements constituting the ceramic sintered body substrate and the thermal spray coating, which reduces the risk of a decrease in the strength of the substrate material or damage to the substrate.
[0018] (9) The present invention also provides a thermal sprayed film-coated member comprising a ceramic sintered body substrate and a thermal sprayed film provided on a surface to be thermal sprayed of the ceramic sintered body substrate, the spatial volume Vvv (μm 3 / μm 2 ), and the ceramics forming the thermal sprayed film. of For average particle diameter D50 (μm), 0.002≦(Vvv / (D50) 3 )≦0.40, and the ceramic sintered body substrate is a SiC sintered body, an AlN sintered body, or an Al2O3 sintered body with a purity of 99.5% or more. This makes it possible to obtain a thermal sprayed film coated member with reduced risk of deterioration in the strength of the substrate material and damage to the substrate.
[0019] (10) In the thermal sprayed film-coated member of the present invention, the ceramic sintered body substrate is a SiC sintered body, an Al2O3 sintered body, or an AlN sintered body, and the thermal sprayed film is made of one or a combination of two or more of alumina, yttria, zirconia, titania, chromia, and yttrium-aluminum-garnet. This makes it possible to obtain a thermal sprayed film-coated member in which the risk of a decrease in the strength of the substrate material and a breakage of the substrate are reduced.
[0020] (11) In the thermal sprayed film-coated member of the present invention, the thermal sprayed film is made of one or a combination of two or more of alumina, yttria, zirconia, titania, chromia, and yttrium-aluminum-garnet, thereby making it possible to obtain a thermal sprayed film-coated member in which the risk of a decrease in the strength of the substrate material and the substrate damage is reduced. Effect of the Invention
[0021] According to the present invention, even if blasting is not performed on a substrate made of a ceramic sintered body, the adhesion strength of the ceramic sprayed film can be improved, and a sprayed film-coated member can be manufactured by forming a ceramic sprayed film while reducing the risk of a decrease in the substrate material strength of the ceramic sintered body substrate or damage to the substrate. [Brief description of the drawings]
[0022] [Figure 1] 1 is a schematic diagram showing a thermal spray coated member according to one embodiment of the present invention. [Diagram 2] 1 is a table showing production conditions and evaluations of Examples and Comparative Examples. [Diagram 3] 1 is a table showing production conditions and evaluations of Examples and Comparative Examples. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0023] As a result of intensive research, the inventors have found that the spatial volume Vvv (μm 3 / μm 2 ) relative to the average particle size D50 of the raw material particles to be sprayed, that is, by adjusting the relationship between the volume of the spray particles and the spatial volume of the substrate so as to satisfy a certain range, it has been discovered that even when blasting is not performed on the substrate made of a ceramic sintered compact, it is possible to improve the adhesion strength of the ceramic sprayed film and to manufacture a sprayed film-coated member having a ceramic sprayed film formed thereon while reducing the risk of a decrease in the substrate material strength of the ceramic sintered compact substrate and damage to the substrate, and thus the present invention has been completed.
[0024] That is, the method for producing a thermal sprayed film-coated member of the present invention is to determine the spatial volume Vvv (μm 3 / μm 2) to a predetermined range, and a coating process for coating the surface to be sprayed of the substrate by plasma spraying with a slurry made of water and a ceramic raw material powder having an average particle diameter D50 in the range of 0.5 μm to 6 μm, wherein the adjusting process is performed to adjust the spatial volume Vvv and the average particle diameter D50 to a value within a range of 0.001≦(Vvv / (D50) 3 The ratio of the thickness of the conductor to the thickness of the conductive layer is adjusted to be within the range of 0.40 or less. Hereinafter, an embodiment of the present invention will be described with reference to the drawings. In the diagrams, the size of each component is shown conceptually and does not necessarily represent the actual dimensional ratio.
[0025] [Method of manufacturing thermal sprayed film coated members] First, a ceramic sintered body substrate is prepared. The ceramic sintered body substrate can be made of various materials. For example, non-oxidizing ceramics such as SiC sintered body, silicon nitride sintered body, and aluminum nitride sintered body, oxides such as Al2O3 sintered body and Y2O3 sintered body, and composite oxides such as YAG can be used. The ceramic sintered body substrate is preferably made of SiC sintered body, AlN sintered body, or Al2O3 sintered body. This makes it possible to form a ceramic spray coating on SiC sintered body, AlN sintered body, or Al2O3 sintered body, which are brittle materials and have poor adhesion to other ceramic materials, while reducing the risk of a decrease in the strength of the substrate material or a substrate breakage.
[0026] The ceramic sintered body substrate may be produced by any method. The production conditions are appropriately selected depending on the type of substrate. For example, a hot press method or HIP can be used. For example, when using a hot press method, a mixed powder of a raw material powder and a sintering aid powder is molded to produce a molded body, which is then fired to produce a sintered body. At this time, for example, the firing temperature is adjusted to be within a temperature range of 1650 to 1950°C, more preferably a temperature range of 1750 to 1900°C. The firing time (the time for which the firing temperature is held) is adjusted to be within a time range of 2 to 10 hours. The pressing pressure during firing is adjusted to be within a pressure range of 1 to 15 MPa. The firing temperature and firing time are also changed depending on the types of raw material powder and sintering aid powder.
[0027] Next, the spatial volume Vvv (μm 3 / μm 2 The surface of the prepared ceramic sintered body substrate to be sprayed is processed by, for example, polishing or grinding to adjust the spatial volume Vvv to a predetermined range. In this specification, the spatial volume Vvv refers to the void volume of the valley portion at a load areal ratio of 80%. Spatial volume Vvv (μm 3 / μm 2 ) can be measured using, for example, a coherence correlation interferometer in accordance with ISO 25178.
[0028] The surface to be sprayed may be processed by blasting, but depending on the abrasive material used and the spraying strength, microcracks may occur in non-metallic substrates such as ceramic sintered substrates. Such cracks may cause a decrease in the strength of the substrate material or damage to the substrate due to the cracks, so great care must be taken when performing blasting. In other words, when performing blasting, it is necessary to perform it in a manner that does not cause cracks, depending on the material of the substrate. Since the method of the present invention does not require roughening of the surface to be sprayed, it is not necessary to perform blasting at a spraying strength that would cause cracks. Therefore, it is also possible to use blasting after adjusting the strength.
[0029] However, since the possibility of problematic cracks occurring is low if polishing or grinding is used, it is preferable to use polishing or grinding when processing the sprayed surface of the ceramic sintered body base material. Also, if the spatial volume Vvv of the sprayed surface of the sintered body is within a predetermined range in the state of the baked surface after sintering, processing is not necessary.
[0030] The surface to be sprayed is adjusted according to the average particle diameter D50 of the ceramic raw material powder contained in the slurry used in the coating process described later, so that the spatial volume Vvv and the average particle diameter D50 are within the range of 0.001≦(Vvv / (D50) 3 )≦0.40. This adjustment may be made by measuring the spatial volume Vvv after processing the surface to be sprayed based on the average particle diameter D50 of the ceramic raw material powder to be used, and if it is not within the above range, further processing the surface to be sprayed. Alternatively, the spatial volume Vvv may be measured after processing the surface to be sprayed, and the ceramic raw material powder to be used may be changed based on the measurement result of the spatial volume Vvv. Note that the spatial volume Vvv (μm 3 / μm 2 ) is preferably 0.01 or more and 0.30 or less.
[0031] Next, a ceramic raw material powder having an average particle size D50 in the range of 0.5 μm to 6 μm and water are prepared and mixed to prepare a slurry. The average particle size D50 of the ceramic raw material powder is preferably 0.5 μm to 6 μm. If D50 is smaller than 0.5 μm, the viscosity of the slurry increases, making thermal spraying difficult and deteriorating the film quality. If D50 is larger than 6 μm, the slurry cannot be transported stably, and the film quality deteriorates. The average particle size D50 can be measured using a dry or wet measurement with a laser diffraction / scattering type particle size distribution measuring device. It is preferable that the particle size distribution of the ceramic raw material powder is sharp.
[0032] The ceramic raw material powder can be made of various materials. Examples of the ceramic raw material powder include alumina (Al2O3), yttria (Y2O3), zirconia (ZrO2), titania (TiO2), chromia (Cr2O3), yttrium aluminum garnet (Y3Al5O 12 It is preferable to use powder of tantalum oxide (Also written as YAG), silicon nitride (Si3N4), silicon carbide (SiC), aluminum nitride (AlN), or any mixed powder of these. These materials are used for various purposes such as protecting the substrate and improving its function, but when the substrate is formed of a ceramic sintered body, adhesion to the substrate may become a problem. The manufacturing method of the present invention can form a ceramic sprayed film using these materials while reducing the risk of a decrease in the strength of the substrate material or damage to the substrate, even when the substrate is formed of a ceramic sintered body.
[0033] The concentration of the slurry is preferably 10 wt% or more and 40 wt% or less, and more preferably 20 wt% or more and 40 wt% or less. If the concentration of the slurry is less than 10 wt%, it takes a long time to apply and the productivity is reduced, which is not industrially feasible. If the concentration of the slurry is more than 40 wt%, the viscosity becomes high and the slurry cannot be transported stably.
[0034] The prepared slurry is then plasma sprayed onto the substrate surface to be coated. The gas used for spraying is preferably a non-oxidizing gas. As the non-oxidizing gas, for example, Ar gas, H2 gas, N2 gas, or a mixed gas of any combination of these gases can be used. The above slurry is supplied to a nozzle via a tube pump and plasma sprayed using the gas.
[0035] Prior to the plasma spraying step, a step of irradiating the substrate surface to be sprayed with plasma using only a gas without adding a slurry may be provided. By providing such a step, the substrate surface to be sprayed is preheated, and the molten ceramic raw material powder is more likely to penetrate into the voids during plasma spraying.
[0036] As a result, as shown in FIG. 1, a ceramic sprayed film 2 is formed from the slurry, covering the sprayed surface 10 of the substrate 1. The thickness of the ceramic sprayed film 2 is preferably adjusted to 50 to 500 μm. If the thickness of the sprayed film 2 is less than 50 μm, there is a high possibility that the functions of the sprayed film 2, such as plasma resistance, abrasion resistance, and heat insulation, may decrease. If the thickness of the sprayed film 2 exceeds 500 μm, the internal stress of the sprayed film 2 increases, increasing the possibility that the adhesion may decrease or peeling may occur. The porosity of the ceramic sprayed film 2 is preferably adjusted to 1 to 5%.
[0037] With this manufacturing method, even if blasting is not performed on the substrate made of a ceramic sintered body, the adhesion strength of the ceramic sprayed film can be improved, and a sprayed film-coated component can be manufactured in which a ceramic sprayed film is formed while reducing the risk of a decrease in the substrate material strength of the ceramic sintered body substrate or damage to the substrate.
[0038] In the manufacturing method of the present invention, since the size of the spatial volume Vvv of the sprayed surface of the ceramic sintered body substrate and the average particle diameter D50 of the raw material powder are compatible, it is presumed that the molten particle diameter of the molten raw material powder particles penetrates into the voids of several μm or less remaining on the surface of the substrate in an appropriate amount, forming pancakes (splats) with these as nuclei and adhering to the substrate. In other words, since the microscopic voids remaining on the surface of the substrate after grinding and polishing generate a micron-scale anchor effect and adhere to the substrate, there is no need to blast the substrate to roughen it, and the risk of inducing cracks in the substrate can be avoided.
[0039] [Thermal spray coating material] The thermal sprayed film-coated member of the present invention comprises a ceramic sintered body substrate and a thermal sprayed film provided on the surface to be thermally sprayed of the ceramic sintered body substrate. 3 / μm 2 ), and the average particle diameter D50 (μm) of the ceramic raw material that forms the sprayed coating, 0.001≦(Vvv / (D50) 3)≦0.40. In addition, there is no chemical bond between the elements that make up the ceramic sintered body substrate and the thermal spray coating.
[0040] The absence of chemical bonds between the elements that make up the ceramic sintered body substrate and the sprayed film refers to a state in which the sprayed film and the substrate are physically attached to each other by the so-called anchor effect. In other words, the molten sprayed particles enter the fine valleys in the substrate and solidify in these valleys. The cooled and solidified sprayed particles exert compressive stress on the substrate, and as a result, the substrate and the sprayed film are in close contact with each other due to the frictional force acting between the substrate and the solidified sprayed particles. The absence of chemical bonds between the elements that make up the ceramic sintered body substrate and the sprayed film can be confirmed by the absence of a reaction layer formed between the ceramic sintered body substrate and the sprayed film.
[0041] In addition, the spatial volume Vvv (μm 3 / μm 2 ) can be measured using a coherence correlation interferometer. 3 / μm 2 ) is a value measured with an areal load ratio of 80%. The average particle diameter D50 (μm) of the ceramic raw material that forms the thermal spray coating can be measured with a particle diameter measuring device using the laser diffraction / scattering method.
[0042] The ceramic sintered body substrate can be selected from various materials. For example, it can be non-oxidizing ceramics such as SiC sintered body, silicon nitride sintered body, and aluminum nitride sintered body, oxides such as Al2O3 sintered body and Y2O3 sintered body, and composite oxides such as YAG. The ceramic sintered body substrate is preferably formed of SiC sintered body, AlN sintered body, or Al2O3 sintered body. This makes it possible to form a sprayed film-coated member in which a ceramic sprayed film is formed on a ceramic sintered body substrate made of SiC sintered body, AlN sintered body, or Al2O3 sintered body, which is a brittle material and has poor adhesion to other ceramic materials, and thus reduces the risk of strength reduction of the substrate material and substrate damage.
[0043] The thermal spray coating is preferably made of one or a combination of two or more of alumina, yttria, zirconia, titania, chromia, and yttrium-aluminum-garnet. This allows the thermal spray coating member to be made with reduced risk of the strength of the substrate material decreasing and the substrate being damaged, making it applicable to a variety of applications. "Made of a combination of two or more" means that the thermal spray coating is formed from a mixture of particles made of different raw materials.
[0044] The thermal sprayed film coated member of the present invention can be a thermal sprayed film coated member in which the risk of a decrease in the strength of the substrate material or damage to the substrate is reduced because the ceramic sintered body substrate and the thermal sprayed film are adhered to each other by the anchor effect.
[0045] [Examples and Comparative Examples] Example 1 (Base material preparation process) The raw SiC powder with a purity of 98% and an average particle size of 0.5μm is mixed with carbon and B4C as sintering aids and an organic binder, and then molded using the CIP (cold isostatic pressing) method to produce a mass of 1ton / cm. 2 The SiC compact was isostatically pressed at 2000°C for 3 hours in a N2 atmosphere to produce a SiC sintered body. The SiC sintered body was then processed into a roughly rectangular plate (or roughly square plate) measuring 100 mm long x 100 mm wide x 5 mm thick to produce a SiC sintered body base material. At this time, one of the main surfaces of the SiC sintered body base material was polished to reduce the spatial volume Vvv (μm 3 / μm 2 ) to 0.010, and the average particle diameter D50 of the raw powder used in the plasma spraying process is set to 0.5 μm, so that (Vvv / (D50) 3 ) was adjusted to 0.0800. The spatial volume Vvv was measured using a coherence correlation interferometer (manufactured by Taylor Hobson). In this manner, the SiC sintered body base material of Example 1 was prepared.
[0046] (Plasma irradiation process) Next, a high-velocity plasma spray machine was used to irradiate or spray a non-oxidizing gas plasma onto the substrate surface to preheat the surface. A mixture of Ar gas, N2 gas, and H2 gas was used as the non-oxidizing gas. The supply of Ar gas to the nozzle of the spray machine was controlled to 100 l / min, the supply of N2 gas was controlled to 70 l / min, and the supply of H2 gas was controlled to 70 l / min.
[0047] The power supplied to the nozzle, which constitutes the high-velocity plasma spraying machine, was adjusted to 65 kW by controlling the applied current to 250 A. The distance between the tip of the nozzle and the substrate surface to be sprayed was adjusted to 75 mm. The scanning speed or displacement speed of the nozzle relative to the substrate was adjusted to 850 mm / s. This generated plasma of a mixed gas of Ar gas, N2 gas, and H2 gas, and this plasma was irradiated or sprayed from the tip of the nozzle onto the substrate surface to be sprayed. Preheating of the substrate surface by plasma irradiation or spraying was carried out for 3 minutes.
[0048] (Plasma spraying process) Then, the Y2O3 slurry was plasma sprayed onto the substrate surface using a non-oxidizing gas by using the high-speed plasma spraying machine as it is. The slurry was prepared by mixing 300 g of Y2O3 raw material powder with a purity of 99.9% or more and an average particle size D50 of 0.5 μm with 700 g of water. A mixed gas of Ar gas, N2 gas, and H2 gas was used as the non-oxidizing gas. The supply amount of Ar gas to the nozzle constituting the spraying machine was controlled to 100 l / min, the supply amount of N2 gas was controlled to 70 l / min, and the supply amount of H2 gas was controlled to 70 l / min. As a result, the spraying speed was controlled to 600 to 700 mm / s.
[0049] The current applied to the nozzle constituting the high-speed plasma spraying machine was controlled to 250A, and the power supplied to the nozzle was adjusted to 65kW. The distance between the tip of the nozzle and the surface of the substrate to be sprayed was adjusted to 75mm. The scanning speed or displacement speed of the nozzle relative to the substrate was adjusted to 850mm / s. This generated a plasma of a mixed gas of Ar gas, N2 gas, and H2 gas, and the raw material powder melted by the plasma was sprayed from the tip of the nozzle onto the surface of the substrate to be sprayed. In this way, the sprayed film-coated member of Example 1 was formed, in which the surface of the SiC sintered compact substrate to be sprayed was coated with a Y2O3 sprayed film.
[0050] Example 2 Example 2 is an example in which the spatial volume Vvv and the average particle diameter D50 are different from those of Example 1. In the substrate preparation step, one of the main surfaces of the SiC sintered substrate to be sprayed is ground to adjust the spatial volume Vvv to 0.190, and the average particle diameter D50 of the raw material powder contained in the slurry is set to 1.0 μm, so that (Vvv / (D50) 3 ) was adjusted to 0.1900. Other than that, a thermal sprayed film-coated member of Example 2 was formed under the same conditions as in Example 1.
[0051] Example 3 Example 3 is an example in which the spatial volume Vvv and the average particle diameter D50 are different from those of Example 1. In the substrate preparation step, one of the main surfaces of the SiC sintered substrate to be sprayed is ground to adjust the spatial volume Vvv to 0.060, and the average particle diameter D50 of the raw material powder contained in the slurry is set to 1.0 μm, so that (Vvv / (D50) 3 ) was adjusted to 0.0600. Other than that, a thermal sprayed film-coated member of Example 3 was formed under the same conditions as in Example 1.
[0052] Example 4 Example 4 is an example in which the spatial volume Vvv and the average particle diameter D50 are different from those of Example 1. In the substrate preparation step, one of the main surfaces of the SiC sintered substrate to be sprayed is ground to adjust the spatial volume Vvv to 0.190, and the average particle diameter D50 of the raw material powder contained in the slurry is set to 3.0 μm, so that (Vvv / (D50) 3 ) was adjusted to 0.0070. Other than that, the thermal sprayed film-coated member of Example 4 was formed under the same conditions as in Example 1.
[0053] Example 5 Example 5 is an example that differs from Example 1 in the type of thermal spray raw material, spatial volume Vvv, and average particle diameter D50. In the substrate preparation process, one of the main surfaces of the SiC sintered substrate to be thermal sprayed is ground to adjust the spatial volume Vvv to 0.190, the type of raw material powder contained in the slurry is Al2O3, and the average particle diameter D50 is 3.0 μm, so that (Vvv / (D50) 3 ) was adjusted to 0.0070. Other than that, the thermal sprayed film coated member of Example 5 was formed under the same conditions as in Example 1.
[0054] Example 6 Example 6 is an example that differs from Example 1 in the type of thermal spray raw material, spatial volume Vvv, and average particle diameter D50. In the substrate preparation process, one main surface of the SiC sintered substrate to be thermal sprayed is ground to adjust the spatial volume Vvv to 0.190, the type of raw material powder contained in the slurry is YAG, and the average particle diameter D50 is 3.0 μm, so that (Vvv / (D50) 3 ) was adjusted to 0.0070. Other than that, the thermal sprayed film-coated member of Example 6 was formed under the same conditions as in Example 1.
[0055] Example 7 Example 7 is an example that differs from Example 1 in the type of thermal spray raw material, spatial volume Vvv, and average particle diameter D50. In the substrate preparation process, one of the main surfaces of the SiC sintered substrate to be thermal sprayed is ground to adjust the spatial volume Vvv to 0.190, the type of raw material powder contained in the slurry is 8 mol% Y2O3-ZrO2, and the average particle diameter D50 is 3.0 μm, so that (Vvv / (D50) 3 ) was adjusted to 0.0070. Other than that, the thermal sprayed film coated member of Example 7 was formed under the same conditions as in Example 1.
[0056] Example 8 Example 8 is an example that differs from Example 1 in the type of thermal spray raw material, spatial volume Vvv, and average particle diameter D50. In the substrate preparation process, one of the main surfaces of the SiC sintered substrate to be thermal sprayed is ground to adjust the spatial volume Vvv to 0.190, the type of raw material powder contained in the slurry is TiO2, and the average particle diameter D50 is 3.0 μm, so that (Vvv / (D50) 3 ) was adjusted to 0.0070. Other than that, the thermal sprayed film coated member of Example 8 was formed under the same conditions as in Example 1.
[0057] Example 9 Example 9 is an example that differs from Example 1 in the type of thermal spray raw material, spatial volume Vvv, and average particle diameter D50. In the substrate preparation process, one main surface of the SiC sintered substrate to be thermal sprayed is ground to adjust the spatial volume Vvv to 0.190, the type of raw material powder contained in the slurry is Cr2O3, and the average particle diameter D50 is 3.0 μm, so that (Vvv / (D50) 3 ) was adjusted to 0.0070. Other than that, the thermal sprayed film-coated member of Example 9 was formed under the same conditions as in Example 1.
[0058] Example 10 (Base material preparation process) Example 10 is an example in which the type of raw material of the substrate, the spatial volume Vvv, and the average particle diameter D50 are different from those of Example 1. MgO and an organic binder were added as sintering aids to Al2O3 raw material powder with a purity of 99.5% and an average particle diameter of 0.5 μm, and the powder was compacted by CIP molding at a density of 1 ton / cm 2 The Al2O3 compact was isostatically pressed at 1600°C for 3 hours to produce an Al2O3 sintered body. The Al2O3 sintered body was then sintered at normal pressure in an air atmosphere at 1600°C for 3 hours to produce an Al2O3 sintered body. The Al2O3 sintered body was then processed into a substantially rectangular plate (or substantially square plate) of 100 mm length x 100 mm width x 5 mm thickness to produce an Al2O3 sintered body base material. At this time, one of the main surfaces of the Al2O3 sintered body base material was ground to adjust the spatial volume Vvv to 0.150. In this way, the Al2O3 sintered body base material of Example 10 was prepared.
[0059] For the Al2O3 sintered body substrate prepared in the above substrate preparation process, the average particle diameter D50 of the Y2O3 raw material powder contained in the slurry was set to 3.0 μm, and (Vvv / (D50) 3 ) was adjusted to 0.0056. Other than that, the thermal sprayed film-coated member of Example 10 was formed under the same conditions as in Example 1.
[0060] Example 11 Example 11 is an example in which the spatial volume Vvv is different from that of Example 1. In the substrate preparation step, one of the main surfaces of the SiC sintered substrate to be sprayed is ground to adjust the spatial volume Vvv to 0.042, thereby reducing the spatial volume Vvv by (Vvv / (D50) 3 ) was adjusted to 0.3360. Other than that, the same conditions as in Example 1 were used to form a thermal sprayed film-coated member of Example 11.
[0061] Example 12 Example 12 is an example in which the spatial volume Vvv and the average particle diameter D50 are different from those of Example 1. In the substrate preparation step, one of the main surfaces of the SiC sintered substrate to be sprayed is ground to adjust the spatial volume Vvv to 0.042, and the average particle diameter D50 of the raw material powder contained in the slurry is set to 1.0 μm, so that (Vvv / (D50) 3) was adjusted to 0.0420. Other than that, a thermal sprayed film-coated member of Example 12 was formed under the same conditions as in Example 1.
[0062] Example 13 Example 13 is an example in which the spatial volume Vvv and the average particle diameter D50 are different from those of Example 1. In the substrate preparation step, one of the main surfaces of the SiC sintered substrate to be sprayed is sandblasted to adjust the spatial volume Vvv to 0.550, and the average particle diameter D50 of the raw material powder contained in the slurry is set to 3.0 μm, thereby (Vvv / (D50) 3 ) was adjusted to 0.0204. Other than that, the same conditions as in Example 1 were used to form a thermal sprayed film-coated member of Example 13.
[0063] Example 14 Example 14 is an example in which the spatial volume Vvv and the average particle diameter D50 are different from those of Example 1. In the substrate preparation process, one of the main surfaces of the SiC sintered substrate to be sprayed is sandblasted to adjust the spatial volume Vvv to 0.550, and the average particle diameter D50 of the raw material powder contained in the slurry is set to 4.5 μm, thereby (Vvv / (D50) 3 ) was adjusted to 0.0060. Other than that, the thermal sprayed film-coated member of Example 14 was formed under the same conditions as in Example 1.
[0064] Example 15 Example 15 is an example in which the spatial volume Vvv and the average particle diameter D50 are different from those of Example 1. In the substrate preparation process, one of the main surfaces of the SiC sintered substrate to be sprayed is sandblasted to adjust the spatial volume Vvv to 0.320, and the average particle diameter D50 of the raw material powder contained in the slurry is set to 3.0 μm, thereby (Vvv / (D50) 3 ) was adjusted to 0.0119. Other than that, the same conditions as in Example 1 were used to form a thermal sprayed film-coated member of Example 15.
[0065] Example 16 Example 16 is an example in which the spatial volume Vvv and the average particle diameter D50 are different from those of Example 1. In the substrate preparation process, one of the main surfaces of the SiC sintered substrate to be sprayed is sandblasted to adjust the spatial volume Vvv to 0.310, and the average particle diameter D50 of the raw material powder contained in the slurry is set to 6.0 μm, thereby (Vvv / (D50) 3 ) was adjusted to 0.0014. Other than that, the thermal sprayed film-coated member of Example 16 was formed under the same conditions as in Example 1.
[0066] Comparative Example 1 Comparative Example 1 is a comparative example in which the spatial volume Vvv is different from that of Example 1. In the substrate preparation step, one of the main surfaces of the SiC sintered substrate to be sprayed is ground to adjust the spatial volume Vvv to 0.060, thereby reducing the spatial volume Vvv by (Vvv / (D50) 3 ) was adjusted to 0.4800. Other than that, the thermal sprayed film coated member of Comparative Example 1 was formed under the same conditions as in Example 1.
[0067] Comparative Example 2 Comparative Example 2 is a comparative example having a different spatial volume Vvv and average particle diameter D50 from Example 1. In the substrate preparation step, one of the main surfaces of the SiC sintered substrate to be sprayed is ground to adjust the spatial volume Vvv to 0.020, and the average particle diameter D50 of the raw material powder contained in the slurry is set to 3.0 μm, thereby (Vvv / (D50) 3 ) was adjusted to 0.0007. Other than that, a thermal sprayed film coated member of Comparative Example 2 was formed under the same conditions as in Example 1.
[0068] Comparative Example 3 Comparative Example 3 is a comparative example having a different spatial volume Vvv and average particle diameter D50 from Example 1. In the substrate preparation step, one of the main surfaces of the SiC sintered substrate to be sprayed is ground to adjust the spatial volume Vvv to 0.042, and the average particle diameter D50 of the raw material powder contained in the slurry is set to 4.5 μm, thereby (Vvv / (D50) 3 ) was adjusted to 0.0005. Other than that, a thermal sprayed film coated member of Comparative Example 3 was formed under the same conditions as in Example 1.
[0069] Comparative Example 4 Comparative Example 4 is a comparative example having a different spatial volume Vvv and average particle diameter D50 from Example 1. In the substrate preparation step, one of the main surfaces of the SiC sintered substrate to be sprayed is ground to adjust the spatial volume Vvv to 0.042, and the average particle diameter D50 of the raw material powder contained in the slurry is set to 6.0 μm, thereby (Vvv / (D50) 3 ) was adjusted to 0.0002. Other than that, a thermal sprayed film coated member of Comparative Example 4 was formed under the same conditions as in Example 1.
[0070] Comparative Example 5 Comparative Example 5 is a comparative example in which the spatial volume Vvv is different from that of Example 1. In the substrate preparation step, one of the main surfaces of the SiC sintered substrate to be sprayed is sandblasted to adjust the spatial volume Vvv to 0.550, thereby reducing (Vvv / (D50) 3 ) was adjusted to 4.4000. Other than that, a thermal sprayed film coated member of Comparative Example 5 was formed under the same conditions as in Example 1.
[0071] Comparative Example 6 Comparative Example 6 is a comparative example having a different spatial volume Vvv and average particle diameter D50 from Example 1. In the substrate preparation step, one of the main surfaces of the SiC sintered substrate to be sprayed is sandblasted to adjust the spatial volume Vvv to 0.550, and the average particle diameter D50 of the raw material powder contained in the slurry is set to 1.0 μm, thereby reducing (Vvv / (D50) 3 ) was adjusted to 0.5500. Other than that, a thermal sprayed film coated member of Comparative Example 6 was formed under the same conditions as in Example 1.
[0072] Comparative Example 7 Comparative Example 7 is a comparative example having a different spatial volume Vvv and average particle diameter D50 from Example 1. In the substrate preparation step, one of the main surfaces of the SiC sintered substrate to be sprayed is ground to adjust the spatial volume Vvv to 0.190, and the average particle diameter D50 of the raw material powder contained in the slurry is set to 6.0 μm, thereby (Vvv / (D50) 3) was adjusted to 0.0009. Other than that, the thermal sprayed film coated member of Comparative Example 7 was formed under the same conditions as in Example 1.
[0073] Comparative Example 8 Comparative Example 8 is a comparative example manufactured by a conventional manufacturing method. In the substrate preparation process, one of the main surfaces of the SiC sintered substrate to be sprayed was sandblasted to adjust the spatial volume Vvv to 1.480, and instead of wet spraying using a slurry, dry spraying was performed in which the raw material powder was sprayed directly with a gas. Granular Y2O3 was used as the raw material powder. The average particle diameter D50 of the granules of the raw material powder was 30.0 μm. Formally, (Vvv / (D50) 3 ) was calculated to be 0.0001.
[0074] (Example 17) Example 17 is an example in which the spatial volume Vvv and the average particle diameter D50 are different from those of Example 10. In the substrate preparation process, one of the main surfaces of the 99.5% purity Al2O3 sintered body substrate to be sprayed is ground to adjust the spatial volume Vvv to 0.161, and the average particle diameter D50 of the Y2O3 raw material powder contained in the slurry is set to 1.0 μm, thereby (Vvv / (D50) 3 ) was adjusted to 0.1610. Other than that, a thermal sprayed film-coated member of Example 17 was formed under the same conditions as in Example 10.
[0075] Comparative Example 9 Comparative Example 9 is a comparative example with a different average particle diameter D50 from Example 17. By setting the average particle diameter D50 of the Y2O3 raw material powder contained in the slurry to 0.5 μm, (Vvv / (D50) 3 ) was adjusted to 1.2880. Other than that, a thermal sprayed film-coated member of Comparative Example 9 was formed under the same conditions as in Example 17.
[0076] (Example 18) Example 18 is an example in which the average particle diameter D50 is different from that of Example 17. By setting the average particle diameter D50 of the Y2O3 raw material powder contained in the slurry to 3.0 μm, (Vvv / (D50) 3) was adjusted to 0.0060. Other than that, a thermal sprayed film-coated member of Example 18 was formed under the same conditions as in Example 17.
[0077] (Example 19) Example 19 is an example with a different average particle diameter D50 from Example 17. By setting the average particle diameter D50 of the Y2O3 raw material powder contained in the slurry to 4.5 μm, (Vvv / (D50) 3 ) was adjusted to 0.0018. Other than that, a thermal sprayed film-coated member of Example 19 was formed under the same conditions as in Example 17.
[0078] Comparative Example 10 Comparative Example 10 is a comparative example with a different average particle diameter D50 from Example 17. By setting the average particle diameter D50 of the Y2O3 raw material powder contained in the slurry to 6.0 μm, (Vvv / (D50) 3 ) was adjusted to 0.0007. Other than that, a thermal sprayed film-coated member of Comparative Example 10 was formed under the same conditions as in Example 17.
[0079] (Example 20) Example 20 is an example that differs from Example 17 in the type of thermal spray raw material and the average particle diameter D50. The thermal spray raw material contained in the slurry is YAG, and the average particle diameter D50 of the YAG raw material powder is 3.0 μm, so that (Vvv / (D50) 3 ) was adjusted to 0.0060. Other than that, a thermal sprayed film-coated member of Example 20 was formed under the same conditions as in Example 17.
[0080] Example 21 Example 21 is an example in which the type of thermal spray raw material and the average particle diameter D50 are different from those of Example 17. The thermal spray raw material contained in the slurry is 8 mol% Y2O3-ZrO2, and the average particle diameter D50 of the 8 mol% Y2O3-ZrO2 raw material powder is 3.0 μm, so that (Vvv / (D50) 3 ) was adjusted to 0.0060. Other than that, a thermal sprayed film-coated member of Example 21 was formed under the same conditions as in Example 17.
[0081] Example 22 Example 22 is an example that differs from Example 17 in the base material, spatial volume Vvv, and average particle diameter D50. In the base material preparation step of Example 17, the Al2O3 raw material powder had a purity of 99.8%. Then, one main surface of the 99.8% purity Al2O3 sintered body base material was ground to adjust the spatial volume Vvv to 0.047, and the average particle diameter D50 of the Y2O3 raw material powder contained in the slurry was set to 0.5 μm, thereby (Vvv / (D50) 3 ) was adjusted to 0.3760. Other than that, a thermal sprayed film-coated member of Example 22 was formed under the same conditions as in Example 1.
[0082] Example 23 Example 23 is an example in which the average particle diameter D50 is different from that of Example 22. By setting the average particle diameter D50 of the Y2O3 raw material powder contained in the slurry to 1.0 μm, (Vvv / (D50) 3 ) was adjusted to 0.0470. Other than that, a thermal sprayed film-coated member of Example 23 was formed under the same conditions as in Example 22.
[0083] (Example 24) Example 24 is an example in which the average particle diameter D50 is different from that of Example 22. By setting the average particle diameter D50 of the Y2O3 raw material powder contained in the slurry to 3.0 μm, (Vvv / (D50) 3 ) was adjusted to 0.0017. Other than that, a thermal sprayed film-coated member of Example 24 was formed under the same conditions as in Example 22.
[0084] Comparative Example 11 Comparative Example 11 is a comparative example with a different average particle diameter D50 from Example 22. By setting the average particle diameter D50 of the Y2O3 raw material powder contained in the slurry to 4.5 μm, (Vvv / (D50) 3 ) was adjusted to 0.0005. Other than that, a thermal sprayed film-coated member of Example 22 was formed under the same conditions as in Example 1.
[0085] Comparative Example 12 Comparative Example 12 is a comparative example with a different average particle diameter D50 from Example 22. By setting the average particle diameter D50 of the Y2O3 raw material powder contained in the slurry to 6.0 μm, (Vvv / (D50) 3 ) was adjusted to 0.0002. Other than that, a thermal sprayed film-coated member of Comparative Example 12 was formed under the same conditions as in Example 22.
[0086] (Example 25) (Base material preparation process) Example 25 is an example in which the type of raw material of the substrate, the spatial volume Vvv, and the average particle diameter D50 are different from those of Example 1. Y2O3 and an organic binder were added as sintering aids to AlN raw material powder with a purity of 98% and an average particle diameter of 0.5 μm, and the powder was molded by CIP molding at a density of 1 ton / cm 2 The AlN compact was isostatically molded at 550°C for 12 hours in an air atmosphere to produce an AlN sintered body. The AlN sintered body was then processed into a substantially rectangular plate (or substantially square plate) of 100 mm length x 100 mm width x 5 mm thickness to produce an AlN sintered body base material. At this time, one of the main surfaces of the AlN sintered body base material was ground to adjust the spatial volume Vvv to 0.158. In this way, the AlN sintered body base material of Example 25 was prepared.
[0087] For the AlN sintered body substrate prepared in the above substrate preparation process, the average particle diameter D50 of the Y2O3 raw material powder contained in the slurry was set to 1.0 μm, and (Vvv / (D50) 3 ) was adjusted to 0.1580. Other than that, the same conditions as in Example 1 were used to form a thermal sprayed film-coated member of Example 25.
[0088] Comparative Example 13 Comparative Example 13 is a comparative example with a different average particle diameter D50 from Example 25. By setting the average particle diameter D50 of the Y2O3 raw material powder contained in the slurry to 0.5 μm, (Vvv / (D50) 3 ) was adjusted to 1.2640. Other than that, a thermal sprayed film-coated member of Comparative Example 13 was formed under the same conditions as in Example 25.
[0089] (Example 26) Example 26 is an example in which the average particle diameter D50 is different from that of Example 25. By setting the average particle diameter D50 of the Y2O3 raw material powder contained in the slurry to 3.0 μm, (Vvv / (D50) 3 ) was adjusted to 0.0059. Other than that, a thermal sprayed film-coated member of Example 26 was formed under the same conditions as in Example 25.
[0090] Example 27 Example 27 is an example in which the average particle diameter D50 is different from that of Example 25. By setting the average particle diameter D50 of the Y2O3 raw material powder contained in the slurry to 4.5 μm, (Vvv / (D50) 3 ) was adjusted to 0.0017. Other than that, the same conditions as in Example 1 were used to form a thermal sprayed film-coated member of Example 25.
[0091] (Example 28) Example 28 is an example that differs from Example 25 in the type of thermal spray raw material and the average particle diameter D50. The thermal spray raw material contained in the slurry is YAG, and the average particle diameter D50 of the YAG raw material powder is 3.0 μm, so that (Vvv / (D50) 3 ) was adjusted to 0.0059. Other than that, the same conditions as in Example 25 were used to form a thermal sprayed film-coated member of Example 28.
[0092] (Example 29) Example 29 is an example that differs from Example 25 in the type of thermal spray raw material and the average particle diameter D50. The thermal spray raw material contained in the slurry is 8 mol% Y2O3-ZrO2, and the average particle diameter D50 of the 8 mol% Y2O3-ZrO2 raw material powder is 3.0 μm, so that (Vvv / (D50) 3 ) was adjusted to 0.0059. Other than that, the thermal sprayed film-coated member of Example 29 was formed under the same conditions as in Example 25.
[0093] (Comparative Example 14) Comparative Example 14 is a comparative example with a different average particle diameter D50 from Example 25. By setting the average particle diameter D50 of the Y2O3 raw material powder contained in the slurry to 6.0 μm, (Vvv / (D50) 3 ) was adjusted to 0.0007. Other than that, a thermal sprayed film-coated member of Comparative Example 14 was formed under the same conditions as in Example 25.
[0094] (Example 30) Example 30 is an example in which the spatial volume Vvv and the average particle diameter D50 are different from those of Example 25. In the substrate preparation process, one of the main surfaces of the AlN sintered substrate to be sprayed is ground to adjust the spatial volume Vvv to 0.042, and the average particle diameter D50 of the Y2O3 raw material powder contained in the slurry is set to 0.5 μm, thereby (Vvv / (D50) 3 ) was adjusted to 0.3360. Other than that, a thermal sprayed film-coated member of Example 30 was formed under the same conditions as in Example 25.
[0095] (Example 31) Example 31 is an example in which the average particle diameter D50 is different from that of Example 30. By setting the average particle diameter D50 of the Y2O3 raw material powder contained in the slurry to 1.0 μm, (Vvv / (D50) 3 ) was adjusted to 0.042. Other than that, a thermal sprayed film-coated member of Example 31 was formed under the same conditions as in Example 30.
[0096] Example 32 Example 32 is an example in which the average particle diameter D50 is different from that of Example 30. By setting the average particle diameter D50 of the Y2O3 raw material powder contained in the slurry to 3.0 μm, (Vvv / (D50) 3 ) was adjusted to 0.0016. Other than that, a thermal sprayed film-coated member of Example 32 was formed under the same conditions as in Example 30.
[0097] (Example 33) Example 33 is an example that differs from Example 30 in the type of thermal spray raw material and the average particle diameter D50. The thermal spray raw material contained in the slurry is YAG, and the average particle diameter D50 of the YAG raw material powder is 3.0 μm, so that (Vvv / (D50) 3 ) was adjusted to 0.0016. Other than that, a thermal sprayed film-coated member of Example 33 was formed under the same conditions as in Example 30.
[0098] (Example 34) Example 34 is an example in which the type of thermal spray raw material and the average particle diameter D50 are different from those of Example 30. The thermal spray raw material contained in the slurry is 8 mol% Y2O3-ZrO2, and the average particle diameter D50 of the 8 mol% Y2O3-ZrO2 raw material powder is 3.0 μm, so that (Vvv / (D50) 3 ) was adjusted to 0.0016. Other than that, a thermal sprayed film-coated member of Example 34 was formed under the same conditions as in Example 30.
[0099] Comparative Example 15 Comparative Example 15 is a comparative example with a different average particle diameter D50 from Example 30. By setting the average particle diameter D50 of the Y2O3 raw material powder contained in the slurry to 4.5 μm, (Vvv / (D50) 3 ) was adjusted to 0.0005. Other than that, a thermal sprayed film-coated member of Comparative Example 15 was formed under the same conditions as in Example 30.
[0100] The sprayed film-coated members of each Example and Comparative Example were evaluated by observing the appearance and measuring the adhesion. The appearance was evaluated by visually checking the presence or absence of cracks and peeling in the sprayed film and the substrate. The adhesion was measured using a φ25 mm test piece in which the sprayed film was formed on the substrate in accordance with JIS H8402. The tables in Figures 2 and 3 show the evaluation results of the sprayed film-coated members of each Example and Comparative Example together with the manufacturing conditions.
[0101] The thermal sprayed film coated members of Examples 1 to 16 had a thermal spray strength of (Vvv / (D50) 3 ) was adjusted to be between 0.001 and 0.40, and both the appearance observation results and the adhesion values were good.
[0102] On the other hand, the thermal sprayed film coated members of Comparative Examples 1, 5, and 6 had a (Vvv / (D50) 3 ) is greater than 0.4. In this case, the results of the appearance observation were fine, but the adhesion value was small. These comparative examples are considered to correspond to cases where the molten particle diameter is too small compared to the Vvv of the substrate, or where the substrate is blasted and Vvv is too large. In such cases, the molten particles penetrate into the narrow parts of the substrate surface and adhere to it, but if left as is, the substrate cannot be covered entirely, and there is a risk of problems such as insufficient voltage resistance characteristics being exhibited. Furthermore, if molten particles are deposited on it, the anchor effect is not fully exhibited and peeling occurs at the sprayed film interface. Therefore, it is presumed that the adhesion to the ceramic sprayed film was not sufficient, especially on the blasted surface of the substrate.
[0103] In addition, the thermal sprayed film coated members of Comparative Examples 2 to 4 and 7 had a (Vvv / (D50) 3 ) is smaller than 0.001. In Comparative Examples 2 to 4, peeling occurred as a result of observing the appearance. Therefore, effective measurement of adhesion was not possible. In Comparative Example 7, the results of observing the appearance were fine, but the adhesion value was small. Comparative Examples 2 to 4 are considered to correspond to the case where the molten particle diameter is too large compared to the Vvv of the substrate. In such a case, the molten particles fill up minute voids of the substrate of several μm or less, and the remaining molten liquid accumulates thickly and solidifies. It is presumed that the anchor portion cannot hold the stress acting during solidification, which causes a phenomenon in which the sprayed film cannot be formed on the substrate. In Comparative Example 7, the surface roughness Ra was larger than that of Comparative Examples 2 to 4, so it is considered that the anchor portion was able to hold the stress acting during solidification, but the surface roughness Ra was not large enough to generate sufficient adhesion, so it is presumed that the adhesion value was small.
[0104] In addition, in Comparative Example 8, the surface roughness Ra was increased by blasting to increase the adhesion strength using the conventional manufacturing method, so the adhesion strength value was high, but the occurrence of cracks was confirmed by observing the appearance.
[0105] The thermal sprayed film coated members of Examples 1 to 15 had Vvv values of 0.01 or more and 0.30 or less, but had an adhesion strength of 10 MPa or more, indicating that even better adhesion strength could be obtained.
[0106] The thermal sprayed film coated members of Examples 17 to 34 are made of an Al2O3 sintered body having a purity of 99.5% or more, an Al2O3 sintered body having a purity of 99.8% or more, or an AlN sintered body, and the (Vvv / (D50) 3 ) was adjusted to be between 0.001 and 0.40, and both the appearance observation results and the adhesion values were good.
[0107] In particular, (Vvv / (D50) 3 ) was 0.002 or more and 0.40 or less, the adhesion strength was high in Examples 1 to 15, 17, 18, 20 to 23, 25, 26, and 28 to 31.
[0108] On the other hand, the thermal sprayed film coated members of Comparative Examples 9 and 13 had a (Vvv / (D50) 3 ) is greater than 0.4. In this case, the results of the appearance observation were fine, but the adhesion value was small. These comparative examples are considered to correspond to cases where the molten particle diameter is too small compared to the Vvv of the substrate, or where the substrate is blasted and Vvv is too large. In such cases, the molten particles penetrate into the narrow parts of the substrate surface and adhere to it, but if left as is, the substrate cannot be covered entirely, and there is a risk of problems such as insufficient voltage resistance characteristics being exhibited. Furthermore, if molten particles are deposited on it, the anchor effect is not fully exhibited and peeling occurs at the sprayed film interface. Therefore, it is presumed that the adhesion to the ceramic sprayed film was not sufficient, especially on the blasted surface of the substrate.
[0109] In addition, the thermal sprayed film coated members of Comparative Examples 10 to 12, 14, and 15 had a (Vvv / (D50) 3) is smaller than 0.002. In this case, in Comparative Examples 10 to 12, 14, and 15, peeling occurred as a result of observing the appearance. Therefore, effective measurement of adhesion was not possible. Comparative Examples 10 to 12, 14, and 15 are considered to correspond to the case where the molten particle diameter is too large compared to the Vvv of the substrate. In such a case, the molten particles fill minute voids of the substrate of several μm or less, and the remaining molten liquid accumulates thickly and solidifies. It is presumed that the anchor portion cannot hold the stress acting during solidification, which causes the phenomenon that the sprayed film cannot be formed on the substrate.
[0110] The present invention is not limited to the above-described embodiment, and it goes without saying that various modifications and equivalents are included within the spirit and scope of the present invention. In addition, the structure, shape, number, position, size, etc. of the components shown in each drawing are for convenience of explanation and may be changed as appropriate. [Explanation of symbols]
[0111] 1. Ceramic sintered body substrate 2. Ceramic spray coating 10. Surface to be sprayed
Claims
1. A method for producing a thermal sprayed film-coated member, comprising the steps of: The spatial volume Vvv (μm) of the sprayed surface of the ceramic sintered body substrate made of a sintered body containing SiC, AlN, or Al 2 O 3 3 / μm 2 ) to a predetermined range; a coating step of coating the surface to be sprayed of the substrate by plasma spraying a slurry made of water and a ceramic raw material powder having an average particle size D50 in the range of 0.5 μm to 6 μm, The adjustment step is performed with respect to the spatial volume Vvv and the average particle diameter D50, 0.001≦(Vvv / (D50) 3 )≦0.40 The method for producing a thermal sprayed film-coated member, comprising adjusting the temperature so that the temperature is within the range of
2. 2. The method according to claim 1, wherein the ceramic sintered body base material is made of a SiC sintered body. The method for producing the above-mentioned thermal sprayed film-coated member is also described.
3. The ceramic sintered body substrate is Al 2 O 3 2. The method for producing a thermal sprayed film-coated member according to claim 1, characterized in that the member is made of a sintered body.
4. 2. The method for producing a thermal sprayed film coated member according to claim 1, wherein the ceramic sintered body base material is made of an AlN sintered body.
5. 5. The method for producing a thermal sprayed film-coated member according to claim 1, wherein a non-oxidizing gas is used in the plasma spraying.
6. 6. The method for producing a thermal sprayed film coated member according to claim 1, wherein the ceramic raw material powder is a powder of alumina, yttria, zirconia, titania, chromia, yttrium aluminum garnet, or a mixture of any of these powders.
7. 7. The method for producing a thermal sprayed film coated member according to claim 1, wherein the spatial volume Vvv is 0.01 or more and 0.30 or less.
8. A thermal sprayed film-coated member comprising a ceramic sintered body substrate and a thermal sprayed film provided on a surface to be thermally sprayed of the ceramic sintered body substrate, The spatial volume Vvv (μm 3 / μm 2 ) and the average particle diameter D50 (μm) of the ceramics forming the thermal spray coating, 0.001≦(Vvv / (D50) 3 )≦0.40 Fulfilling the ceramic sintered body base is a sintered body containing SiC, AlN, or Al 2 O 3 , A thermal sprayed film-coated member, characterized in that no chemical bond exists between the elements constituting the ceramic sintered body substrate and the thermal sprayed film.
9. A thermal sprayed film-coated member comprising a ceramic sintered body substrate and a thermal sprayed film provided on a surface to be thermally sprayed of the ceramic sintered body substrate, The spatial volume Vvv (μm 3 / μm 2 ) and the average particle diameter D50 (μm) of the ceramics forming the thermal spray coating, 0.002≦(Vvv / (D50) 3 )≦0.40 Fulfilling The ceramic sintered body substrate is a SiC sintered body, an AlN sintered body, or an AlN sintered body having a purity of 99.5% or more. 2 O 3 A thermal sprayed film-coated member, characterized in that it is a sintered body.
10. The ceramic sintered body substrate is made of a SiC sintered body, an Al 2 O 3 a sintered body or an AlN sintered body, 9. The member coated with a thermal spray film according to claim 8, wherein the thermal spray film is made of one or a combination of two or more of alumina, yttria, zirconia, titania, chromia, and yttrium aluminum garnet.
11. 10. The member coated with a thermal-sprayed film according to claim 9, wherein the thermal-sprayed film is made of one or a combination of two or more of alumina, yttria, zirconia, titania, chromia, and yttrium-aluminum-garnet.
Citation Information
Patent Citations
Member coated with ceramic sprayed coating excellent in film adhesion
JP2014162934A
Plasma resistant member
JP2017114724A
Slurry for spray, and formation method of spray coating
JP2018154895A
Manufacturing method of spray coated member
JP2019127598A
Manufacturing method of flame spray film coated member
JP2021025093A